Healing culture: Strategi menjaga kesehatan mental dan keseimbangan akademik generasi z - ADAWIYAH, SITI ROBIATUL (Maliki Interdisciplinary Journal, 2025)
Nowadays, the term healing is often used by Generation Z. This activity is no longer seen as a mere trend, but is considered an important way to maintain mental health amidst increasingly challenging life. Generation Z is now more easily stressed, anxious, and even sad due to the pressure of academic demands they experience. This study aims to determine how healing affects the mental health of Generation Z. This study was conducted by reading various sources that explain how Generation Z seeks ways to calm themselves and how they deal with stress related to mental conditions that occur in their lives. The results of the study show that healing culture provides positive benefits in the form of improved stress management and reduced anxiety. Thus, healing culture plays a significant role in the mental health of Generation Z, but its impact greatly affects life depending on how each person adapts healing activities to their own needs and maintains balance in facing daily problems.